Teachers’ Attitudes toward the Merdeka Curriculum in Elementary Schools in Pematangsiantar - Marpaung, Tiarma Intan; Sihombing, Marino; Irwansyah, Syalaisha Syafira; Sinaga, Venyta; Parhusip , Nadya; Siburian, Tria; S, Leony Elisabeth; Sitanggang, Loria Vikki; Simbolon, Selina Grace Kaizura (Innovative: Journal Of Social Science Research, 2025)
The implementation of the Merdeka Curriculum in Indonesia marks a significant shift in educational policy, emphasizing flexibility and student-centered learning. This study investigates elementary school teachers' attitudes towards this new curriculum in Pematangsiantar, aiming to understand its practical implementation and challenges. Using a mixed-methods approach, data was collected from 20 randomly selected teachers through Google Forms questionnaires and semi-structured interviews. The questionnaire, based on a 5-point Likert scale, comprised 20 statements assessing cognitive understanding, affective engagement, and psychomotor application of the curriculum. Results show that 80-90% of teachers demonstrate a high level of understanding and positive engagement with the curriculum's principles. Qualitative analysis revealed teachers' enthusiasm for the curriculum's flexibility but highlighted concerns about resource limitations and the need for ongoing professional development. The study concludes that while teachers are generally receptive to the Merdeka Curriculum, targeted support and resources are crucial for its successful implementation. These findings provide valuable insights for educational policymakers and school administrators in refining curriculum implementation strategies.